1983
DOI: 10.1039/c39830000290
|View full text |Cite
|
Sign up to set email alerts
|

On the stereochemistry of ethylene biosynthesis

Abstract: The conversion of (i) an equal mixture of the two isomers of cis-2,3-dideuterio-l -aminocyclopropanecarboxylate or (ii) ( &)-trans-2,3-dideuterio-l -aminocyclopropanecarboxylate by apple slices gave in both cases a 1 :I mixture of cis-and trans-I ,2-dideuterioethylene; in contrast the chemical oxidation (NaOCI) of these substances proceeded with complete retention of configuration to cis-dideuterioethylene and trans-dideuterioethylene, respectively.The plant hormone ethylene is derived from methionine via 1ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 1 publication
0
34
0
Order By: Relevance
“…Recently, Pirrung (30) has studied the electrochemical oxidation of ACC, which leads to ethylene formation with loss of stereochemistry, as observed in apple tissue (28). In this model reaction, C-1 of ACC also yields cyanide.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pirrung (30) has studied the electrochemical oxidation of ACC, which leads to ethylene formation with loss of stereochemistry, as observed in apple tissue (28). In this model reaction, C-1 of ACC also yields cyanide.…”
Section: Discussionmentioning
confidence: 99%
“…4 In contrast, the efficient chemical oxidation of (2) with sodium hypochlorite gave cis-[ 1 ,2-2H2]ethylene with retention of configuration. 3 We have now found that the biosynthetic stereochemical result can be duplicated by oxidation of ACC with various transition metal ions, such as Cu2+, Mn04-, and Fe042-, Table 1. That the amino group is the site of reaction in these processes was indicated by the absence of reaction of ACC in acidic media and further by the observation that whereas cyclopropylamine (lb) gave ethylene (9%) with CuS04, neither the N-ethoxycarbonyl-ACC (4) nor cyclopropanecarboxylic acid produced ethylene when oxidized under the same conditions.…”
mentioning
confidence: 89%
“…245, 246 Mass spectrometry was used by Masamune and co-workers to establish the sequence of production of stress metabolites by tubers of potato (Solanurn t u b e r ~s u r n ) . ~~~ These researchers determined that the laevorotatory isomer of ( f )-[8,8-2H2]solavetivone (232) is converted sequentially into lubimin (233), oxylubimin (234), and finally rishitin (235). The studies by Dewick and co-workers on the biosynthesis of isoflavanoids in red clover (Trifoliurn pratense) provide numerous representative examples of the use of mass spectrometry to study the incorporation of deuteriated advanced precursors.…”
Section: Detection By Mass Spectrometrymentioning
confidence: 99%
“…This is in accord with the usual retention of up to three hydrogen atoms of acetate in a polyketide starter unit but with the substantial loss of such protons, by exchange, from subsequent units. The mechanism of formation of lubimin (233), hydroxylubimin (234), and rishitin (235) in potato tubers that are infected with Monifinia fructicola (see also Sections 4.2.2 and 4.5.2) was examined, using [2-13C,2H3]a~etate.308 Because of exchange processes that occur during the metabolism of acetate, the proton-decoupled 13C n.m.r. spectra of these compounds display complex upfield multiplets for many of the carbons that have been derived from C-2 of acetate.…”
Section: Deuterium That Is Directly Attached To 13cmentioning
confidence: 99%